Taxonomy and phylogeny of Paradictyoarthrinium salsipaludicola sp. nov. (Paradictyoarthriniaceae, Pleosporales) from mangroves - Htet, Zin Hnin; Prematunga, Chasika; Mapook, Ausana; Jones, E.b. Gareth; Chethana, K.w. Thilini (Phytotaxa, 2023)
A new fungal species found on decaying wood in a mangrove habitat is described. The analysis of combined LSU, ITS, and rpb2 sequence data revealed that it belongs to the family Paradictyoarthriniaceae (Pleosporales). Maximum likelihood and Bayesian analyses were used to determine the taxon’s phylogenetic affinities. The novel species is typical of Paradictyoarthrinium in its gregarious, black, powdery colonies with macronematous conidiophores and unevenly dictyoseptate, muriform, green to brown conidia. The new taxon is compared to other Paradictyoarthrinium species, and a detailed morphological description and illustration are provided.